A high-strength lightweight thermal insulation castable and preparation method thereof
Through the modification technology of the denitrifying bacterial solution to generate calcium carbonate filled expanded perlite, combined with ceramic and fiber materials, the problem of high water absorption rate of expanded perlite is solved, the mechanical and thermal insulation properties of the castable are improved, and the resistance of the castable is achieved. Improved thermal shock stability and thermal insulation performance.
Patent Information
- Application Number
- CN202311717320.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-12-14
- Publication Date
- 2024-12-13
- Estimated Expiration
- 2043-12-14
AI Technical Summary
The high water absorption rate of expanded perlite in existing refractory castables leads to a decrease in mechanical properties and thermal insulation properties, and modification methods such as hydrophobic agent treatment and surface coating increase bulk weight, resulting in an increase in thermal conductivity and a decrease in thermal insulation properties.
The expanded perlite is soaked first and then sprayed to form calcium carbonate-filled pores, combined with ceramic granules, pure calcium aluminate cement, silicon sol and fiber materials, and optimize the modification of expanded perlite to form high strength , light aggregate with low water absorption rate, and through the combination of pre-synthetic light aggregate and ceramic granules, the thermal shock resistance and thermal insulation performance of the castable are improved.
It significantly improves the mechanical properties and refractory insulation properties of the castable material, reduces the water absorption rate and thermal conductivity, enhances the thermal shock resistance and thermal insulation performance, and ensures the effectiveness of the castable material at high temperatures.
Smart Images

Figure BDA0004606382560000161
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of refractory materials, and in particular relates to a high-strength lightweight thermal insulation castable and a preparation method thereof. Background Art
[0002] Refractory castables are the most widely produced and used amorphous refractory materials, mainly used to construct various heating furnace linings and other integral structures. It is a granular and powdery material made of refractory substances, and a certain amount of binder and water are added to form it. It has high fluidity, is suitable for construction by pouring methods, and is an amorphous refractory material that can be hardened without heating. It is composed of refractory aggregates, powders, binders, admixtures, water or other liquid materials. It is generally cast and formed by pouring, vibrating or tamping at the site of use, and can also be made into prefabricated parts for use.
[0003] Perlite is a volcanic rock, the main components of which are SiO2 (70-75%) and other oxides (K2O, Al2O3, etc.). Under high temperature conditions (usually 800-1200°C), its volume can expand 10-30 times, thus producing expanded perlite. Expanded perlite has good physical and chemical properties such as light weight, porous, non-toxic, soundproof, acid and alkali resistant, and corrosion resistant. It is widely used in thermal insulation castables, construction, chemical raw material production, animal husbandry and other fields, especially as a component of lightweight aggregate in thermal insulation castables or other refractory materials.
[0004] The Chinese patent with publication number CN113185310A discloses an aluminum-silicon castable with floating beads and a preparation method thereof, comprising the following raw materials: the calcium aluminate cement has a proportion of 30% to 46%, the silicon powder has a proportion of 1% to 6%, the perlite aggregate has a proportion of 40% to 45%, the sinking beads have a proportion of 3% to 8%, and the floating beads have a proportion of 0% to 16%. The aluminum-silicon castable with floating beads and a preparation method thereof described in the patent uses lightweight perlite as aggregate, adds silicon powder, sinking beads and other fine particles, and adds an appropriate amount of floating beads to significantly improve the thermal conductivity. The floating beads have a small bulk density and a spherical shape, which is more conducive to increasing the fluidity between the raw materials of the castable. The floating beads themselves have a large specific surface area in the castable and high reaction activity, which is conducive to improving the combination between the raw materials, increasing the strength, and the volume density thereof. They can form a uniform gas phase connection structure with the lightweight porous perlite, thereby reducing the thermal conductivity and improving the thermal insulation effect. However, the castable in this patent uses perlite as lightweight aggregate. Due to the high water absorption rate and low cylinder pressure strength of perlite, it is easy to break during mixing, transportation and handling, thereby affecting the performance of the perlite lightweight aggregate. The deterioration of aggregate performance not only leads to an increase in consumption, but also leads to a decrease in the mechanical properties of the castable. In addition, the thermal insulation performance of the castable in this patent needs to be further improved.
[0005] The Chinese patent with publication number CN102424588A discloses a refractory castable, including aggregate, powder and binder, wherein the mass ratio of the aggregate to the powder is 3:2, the binder is 10-15% of the total weight of the aggregate and the powder, the aggregate is corundum particles with an average particle size of 2.0-3.0 mm and expanded perlite, and the powder is 200-300 mesh SiO2 ultrafine powder. The corundum particles are composed of the following corundum particles with different particle size ranges: 4.0-3.0 mm accounts for 50%, 1.0-0.5 mm accounts for 40%, and 0.5-0.2 mm accounts for 10%. The binder is CA-70 aluminate cement or α-Al2O3. The technical effect of this patent is: the refractory castable of this patent has a small volume density, low conductivity, good thermal insulation, and high strength at room temperature. It is a material with high value for preparing large and special-shaped refractory products. The patent has reasonable material selection, which can greatly reduce the maintenance workload and shorten the construction period. However, this patent uses expanded perlite and corundum particles as aggregates. Although expanded perlite is a lightweight aggregate with good refractory and thermal insulation properties, it expands rapidly at high temperatures and can improve the density of the internal structure of the castable, but the expanded perlite has the disadvantage of high water absorption. When preparing the castable, it absorbs water in the early stage and loses water in the later stage, resulting in large volume shrinkage and deformation, which affects its use effect, and then reduces the mechanical properties and refractory and thermal insulation properties of the castable. Therefore, it is particularly important to modify perlite or expanded perlite.
[0006] At present, most of the methods for modifying expanded perlite are mainly to reduce the water absorption rate of perlite and improve its strength by treating it with a hydrophobic agent and coating it with inorganic or organic matter. However, the improvement effect of hydrophobic agent treatment on the strength of expanded perlite is not obvious, and the surface coating method is mainly used to improve the strength of expanded perlite. Although the coating treatment of expanded perlite with polymer or cement-based materials has obvious improvements in the strength and water absorption rate of perlite, this modification treatment increases the bulk density of expanded perlite to a certain extent, and increases the volume density of the castable as an aggregate, thereby causing the thermal conductivity of the castable to increase and the thermal insulation performance to decrease. Therefore, it is a technical problem that needs to be solved urgently to study a new type of modified expanded perlite as a lightweight aggregate for use in castables, so that the castable has the characteristics of stable performance, light bulk density, good mechanical properties, excellent thermal insulation performance and thermal shock resistance. Summary of the invention
[0007] In order to solve the problems existing in the prior art, the purpose of the present invention is to provide a high-strength lightweight thermal insulation castable and a preparation method thereof. The present invention uses the modified expanded perlite lightweight aggregate as the main component to prepare the castable, so that the castable has stable performance, light bulk density, good mechanical properties, and also has excellent thermal insulation performance and thermal shock resistance stability.
[0008] In order to achieve the above object, the present invention adopts the following technical solution:
[0009] A high-strength, lightweight, thermally insulating castable, characterized in that the castable comprises the following raw materials in percentage by weight: 20 to 45 parts of modified expanded perlite, 10 to 35 parts of ceramsite, 3 to 8 parts of silica powder, 8 to 15 parts of pure calcium aluminate cement, 10 to 20 parts of fly ash, 5 to 15 parts of coke gemstone powder, 0.1 to 0.2 parts of water reducer, 0.1 to 0.15 parts of silica sol as a binder, 2 to 4 parts of chopped zirconium-containing refractory fibers, 0.5 to 1 parts of heat-resistant stainless steel fibers, 0.8 to 1.5 parts of explosion-proof fibers, 4 to 8 parts of calcium carbonate powder, and 8 to 12 parts of kyanite powder.
[0010] Preferably, the preparation method of the modified expanded perlite is as follows:
[0011] (1) soaking the expanded perlite in a bacterial solution of denitrifying bacteria for 18 to 24 hours, adding a calcium ion nutrient solution to the bacterial solution, and continuing to soak for 8 to 12 hours, then taking out the expanded perlite, washing it, drying it, and setting it aside;
[0012] (2) The expanded perlite washed and dried in step (1) is spread flat in a glass container of 30 cm in length×20 cm in width×9 cm in height, and then the surface of the expanded perlite is sprayed with a denitrifying bacteria solution and a calcium ion nutrient solution of the same concentration as in step (1) in sequence, once every 6 to 8 hours, and sprayed 4 to 6 times to obtain modified expanded perlite.
[0013] Specifically, expanded perlite is made of high-quality acidic volcanic glass rock, which is crushed, dried, put into a high-temperature roasting furnace, and expanded instantly. However, the existing expanded perlite has poor flexibility, high brittleness, poor water resistance, and high water absorption. It is easy to break during mixing or transportation, which leads to a decrease in the mechanical properties and thermal insulation properties of lightweight aggregates. However, lightweight aggregates are an important component of castables, and the decline in the performance of lightweight aggregates will directly lead to a decrease in the mechanical properties and thermal insulation properties of castables. The present application uses a microbial liquid to soak the expanded perlite first and then spray it to obtain the modified expanded perlite. First, soak the expanded perlite in the bacterial solution of denitrifying bacteria. The bacterial solution will gradually adsorb or deposit in the internal pores of the expanded perlite. With the addition of calcium ion nutrient solution, the bacterial solution will immediately mineralize and deposit with the calcium ions in the calcium ion nutrient solution in the internal pores of the expanded perlite to produce calcium carbonate, which will fill some of the pores inside the expanded perlite. The main function of denitrifying bacteria is to induce the production of calcium carbonate to fill the pores inside the expanded perlite. The production of calcium carbonate is concentrated around the denitrifying bacterial solution. The calcium ion solution provides calcium ions and nutrients for the survival of denitrifying bacteria and the production of calcium carbonate. The first step is to soak the expanded perlite in the denitrifying bacterial solution. The main purpose is to greatly increase the pores inside the expanded perlite. The concentration of denitrifying bacteria in the pores is increased, so that the denitrifying bacteria are adsorbed on the inner wall of the pores inside the expanded perlite. With the addition of calcium ion nutrient solution, the calcium carbonate produced can fill the pores inside the expanded perlite. The second step is to spread the expanded perlite in a glass container, and then spray the denitrifying bacteria solution and calcium ion nutrient solution on the surface of the expanded perlite in turn. Its main function is to enable the bacteria solution to contact the calcium ion nutrient solution in time and to be evenly distributed on the surface of the expanded perlite, so that the bacteria can have better activity in a suitable environment. The surface of the expanded perlite serves as the nucleation site of the denitrifying bacteria. The microorganisms are more active and produce calcium carbonate faster, so that more calcium carbonate is precipitated on the surface of the expanded perlite to fill the pores on its surface. At the same time, since the expanded perlite has a relatively small bulk density, most of the expanded perlite floats on the surface of the bacterial solution or squeezes together when immersed in the denitrifying bacterial solution, resulting in that many of the expanded perlite's internal and surface pores cannot absorb the bacterial solution, thereby affecting the later generation of calcium carbonate. Since the present application reduces the water absorption rate of the expanded perlite and improves the mechanical strength while ensuring that its bulk density is not too large, the present application first spreads the perlite in a glass container in the second step, and then sprays the denitrifying bacterial solution and the calcium ion nutrient solution on the surface of the expanded perlite in sequence. This can make up for the defect that some of the expanded perlite in the first step floats on the surface of the bacterial solution or is squeezed together, resulting in the internal and surface pores of the expanded perlite not being filled. On the other hand, the number and frequency of spraying can be controlled to ensure that the amount of calcium carbonate generated is not too much, which leads to an increase in the bulk density of the expanded perlite.The present application adopts the method of first soaking and then spraying the bacterial solution to modify the expanded perlite so that the bacterial solution is adsorbed in the internal or surface pores of the expanded perlite, which to a certain extent avoids the phenomenon of instantaneous contact charge repulsion and inability to attach caused by the negative charge on the surface of the expanded perlite and the negative charge on the denitrifying bacteria themselves, and can ensure that the denitrifying bacteria provide more nucleation sites, so that more calcium carbonate is precipitated on the surface and internal pores of the expanded perlite, filling the pores of the expanded perlite, thereby reducing the water absorption rate of the expanded perlite and improving its mechanical properties.
[0014] Denitrifying bacteria are a type of bacteria that exist in large quantities in sewage and soil. They can use nitrate (nitrogen source) and various organic matter (carbon source) to generate energy to maintain their own metabolism under anaerobic conditions. The principle of using denitrifying bacteria to modify expanded perlite in this application is as follows:
[0015] (CH3COO)2Ca+Ca(NO3)2→CaCO3↓+H2O+N2↑+CO2↑;
[0016] Preferably, the bacterial liquid of denitrifying bacteria is prepared by the following method: inoculating the strain of nitrifying bacteria into a trypsin culture medium, culturing at a temperature of 25 to 35° C. for 18 to 24 hours, then centrifuging the culture medium to obtain denitrifying bacteria, adding distilled water to the obtained denitrifying bacteria and mixing them evenly to obtain a bacterial liquid of denitrifying bacteria.
[0017] Preferably, the concentration of denitrifying bacteria in the denitrifying bacteria solution is 2×10 8 ~4×10 8 cfu / mL; the denitrifying bacteria is Pseudomonas stutzeri BBW831 or Pseudomonas denitrificans ATCC13867.
[0018] Preferably, the calcium ion nutrient solution is a mixture of 25-50 g / L calcium acetate, 15-25 g / L calcium nitrate and 1-12 g / L glucose, wherein the carbon-nitrogen mass ratio in the calcium ion nutrient solution is (4-8):1, and the solvent of the calcium ion nutrient solution is distilled water; the mass ratio of the denitrifying bacteria liquid to the calcium ion nutrient solution is 1:(1-1.5).
[0019] Specifically, the present application adopts denitrifying bacteria to carry out microbial mineralization. The denitrification process will produce nitrogen and water vapor, which are non-toxic and harmless substances. Moreover, the nitrogen source, carbon source required for the denitrification process and the calcium source required for the formation of calcium carbonate can be provided by calcium nitrate and calcium acetate respectively, and other anions will not be introduced, and there will be no negative impact on expanded perlite aggregate and steel castables. At the same time, the addition of glucose is to enhance the activity of denitrifying bacteria in adverse environments.
[0020] Preferably, the mass ratio of modified expanded perlite to ceramsite is (1.1-3):1.
[0021] Preferably, the silicon micropowder has a SiO2 content of ≥95wt% and a particle size of 1.0μm to 1.8μm; and the pure calcium aluminate cement has an Al2O3 content of ≥80wt%.
[0022] Preferably, the particle size of the expanded perlite is 0.5-2.8 mm, the particle size of the ceramsite is 0.5-6 mm, the particle size of the fly ash is 1.5-5 μm, the particle size of the pyrope fine powder is 0.1-1 mm, the particle size of the calcium carbonate micropowder is 100-130 mesh, and the particle size of the kyanite fine powder is 80-120 mesh.
[0023] Preferably, the length of the short fiber flocs in the short-cut zirconium-containing refractory fibers is 5 to 10 mm; the heat-resistant stainless steel fibers are heat-resistant steel fibers containing nickel-chromium alloy elements; and the explosion-proof fibers are polypropylene fibers with a diameter of 1.5 to 3 μm and a length of 3 to 5 mm.
[0024] By adding short-cut zirconium-containing refractory fibers and heat-resistant stainless steel fibers together, and utilizing the high-temperature elastic-plasticity and fiber drawing toughening mechanism of heat-resistant stainless steel fibers, the fracture toughness and thermal shock stability of the castable are improved, and the castable's ability to resist mechanical damage is enhanced; the high melting point, drawing toughening and excellent thermal insulation properties of short-cut zirconium-containing refractory fibers are utilized to improve the thermal shock stability and thermal insulation properties of the castable; by optimizing the addition amount of the above two types of fibers, the adverse effects of increased thermal conductivity, high-temperature oxidation, and increased volume density caused by the addition of heat-resistant stainless steel fibers are suppressed, and the castable's resistance to thermal mechanical stress is further improved. Damage capacity; due to the low porosity of the castable, the material permeability is reduced, and the low thermal conductivity makes the temperature distribution inside the castable uneven, resulting in the possibility of the castable bursting. In this application, explosion-proof fibers are added to the castable. The explosion-proof fibers will soften, shrink, and melt during the high-temperature use of the castable, and finally form pores and carbonize, forming tiny network pores inside the castable material, opening the water and gas channels, reducing the internal stress of the castable material, preventing the castable from bursting, and increasing the service life of the castable; strengthening the synergistic effect of the three fibers, improving the comprehensive performance of the castable,
[0025] Preferably, the water reducer is a composite water reducer, which is a mixture of FDN high-efficiency water reducer, calcium lignin sulfonate and sodium tripolyphosphate, and the weight ratio of the FDN high-efficiency water reducer, calcium lignin sulfonate and sodium tripolyphosphate is (4.5-6):(1-1.5):(2-3).
[0026] The compound combination of three water reducers, namely FDN high-efficiency water reducer, calcium lignin sulfonate and sodium tripolyphosphate, avoids the performance shortcomings of a single water reducer, reduces the amount of water added to the castable, and enables the castable to achieve a high water reduction rate without segregation, thereby improving the fluidity and mechanical properties of the castable.
[0027] Preferably, a method for preparing the above-mentioned high-strength lightweight thermal insulation castable comprises the following steps:
[0028] Step S1, preparing materials according to the raw material components and weight percentages of high-strength lightweight thermal insulation castable;
[0029] Step S2, adding the modified expanded perlite, calcium carbonate powder, kyanite powder, binder silica sol, and pure calcium aluminate cement into a mixer according to the weight percentage prepared in step S1, stirring and mixing evenly to obtain a mixture, drying the mixture at 80-200° C. for 8-15 hours, and cooling to room temperature after drying to obtain a pre-synthesized lightweight aggregate;
[0030] Step S3, mixing the remaining raw materials with the pre-synthesized lightweight aggregate obtained in step S2 in a corresponding proportion to obtain a high-strength lightweight thermal insulation castable.
[0031] Compared with the prior art, the present invention has the following positive and beneficial effects:
[0032] (1) The present invention utilizes the bacterial solution of microorganisms to soak the expanded perlite first and then spray it to obtain the modified expanded perlite; first, the expanded perlite is soaked in the bacterial solution of denitrifying bacteria to greatly increase the concentration of denitrifying bacteria in the pores inside the perlite, so that the denitrifying bacteria are adsorbed on the inner wall of the pores inside the expanded perlite, and with the addition of calcium ion nutrient solution, the calcium carbonate produced thereafter can fill the pores inside the expanded perlite; then, the denitrifying bacterial solution and the calcium ion nutrient solution are sprayed on the expanded perlite in sequence so that the bacterial solution can contact the calcium ion nutrient solution in time, so that the bacteria can have better activity in a suitable environment, and the surface of the expanded perlite serves as a nucleation site for the denitrifying bacteria, so that the activity of the nitrifying bacteria is better and the speed of producing calcium carbonate is faster, so that more calcium carbonate is precipitated on the surface of the expanded perlite to fill the pores on its surface. This treatment method avoids the instantaneous contact charge mutual repulsion and inability to attach due to the negative charge on the surface of the expanded perlite and the negative charge on the denitrifying bacteria themselves, and can ensure that the denitrifying bacteria provide more nucleation sites, so that more calcium carbonate is precipitated on the surface and internal pores of the expanded perlite, filling the pores of the expanded perlite, thereby reducing the water absorption rate of the expanded perlite and improving its mechanical properties. When the modified expanded perlite is mixed with calcium carbonate powder, kyanite powder, silica sol, and pure calcium aluminate cement to prepare a pre-synthesized lightweight aggregate, the strength of the aggregate is significantly improved and the water absorption rate of the aggregate is reduced, thereby also improving the mechanical properties and fire-resistant insulation properties of the castable to a certain extent. Especially when the castable is used at high temperature (above 900°C), the calcium carbonate powder added in the present application decomposes at high temperature to obtain CaO, which reacts with the alumina in pure calcium aluminate cement in situ to generate calcium hexaaluminate after high-temperature calcination. The particle size of calcium hexaaluminate is much smaller, and the dispersibility of the generated flaky calcium hexaaluminate is greatly improved, so that a large number of evenly distributed tiny voids and cracks are formed in the castable matrix; at the same time, in the process of calcium carbonate powder decomposing at high temperature to generate CaO and CO2, the escape of CO2 leads to the formation of a large number of evenly distributed micropores in the castable system, thereby significantly improving the thermal shock stability of the castable.
[0033] (2) Kyanite powder is added to the pre-synthesized lightweight aggregate of the present application, and the characteristic of kyanite decomposing and expanding at 1100°C to generate mullite and quartz is utilized to make up for the deficiency of high-temperature sintering shrinkage of lightweight castables, improve the high-temperature volume stability of castables, and avoid cracking and damage caused by high-temperature shrinkage; at the same time, the modified expanded perlite and ceramsite in the present application are combined to obtain a composite aggregate. The CaO, MgO, and Na2O in the ceramsite can act as sintering aids, which is beneficial to the sintering densification of the castable. The addition of an appropriate amount of ceramsite can react with the modified perlite to generate CaSiO3, which has high strength and durability and can improve the room temperature stability of the castable. Compressive strength and thermal shock resistance; however, excessive addition of expanded clay will deteriorate the hydration effect of pure calcium aluminate cement, reduce the bonding phase between aggregates, and lead to a decrease in the compressive strength of the castable, so the mass ratio of modified expanded perlite to expanded clay is controlled to be (1.1-3):1 in this application; and due to the low cost, low thermal conductivity, low density, and high cylinder pressure strength of expanded clay, the raw material cost of lightweight castables and the volume density of castables are reduced, and the thermal insulation performance and thermal shock stability of castables are improved; through the optimization of the addition ratio of the two lightweight aggregates and their coupled synergistic effect, the stable support of aggregates in the castable is achieved, and the strength, thermal shock stability, and thermal insulation performance of the castable are improved.
[0034] (3) The present application adds pure calcium aluminate cement, silica sol and silica powder as binders. Silica sol is used as a binder for castables mainly through the condensation reaction between silica sol particles (Si-OH+HO-Si=Si-O-Si+H2O) to promote the coagulation and hardening of the castable during the curing process. Since only the bonds between the silica sol particles change in this reaction process and no hydration products are produced, the silica sol-bonded castable does not have a significant strength reduction in the medium and low temperature range. Since the silica sol has good air permeability, the castable bonded therewith is not prone to bursting during baking (even rapid baking). In addition, the silica sol-bonded castable also has good sintering performance, good volume stability, high high temperature strength, good slag resistance and good thermal shock resistance. Pure calcium aluminate cement has a high alumina content and relatively low impurity components, especially In particular, the reasonable combination of monocalcium aluminate and dicalcium aluminate has high bonding strength and stable setting time, which makes the castable have very high strength; silicon micropowder is used as a binder to bond fine powder and aggregate through the hydration of pure calcium aluminate cement. Silicon micropowder can fill the gaps between pure calcium aluminate cement particles and react with hydration products to form a gel, which improves the bonding strength between aggregate and fine powder while reducing pores and improving the mechanical properties of aggregate; pure calcium aluminate cement, silica sol and silicon micropowder are used as composite binders to improve the bonding performance between aggregates, and at the same time, they can also improve the high-temperature strength and thermal shock resistance of the castable; and coke stone powder and fly ash powder with high hardness and high refractoriness are used as fine powder to fill the gaps between aggregates. Due to the uneven surface of aggregates, the contact specific surface area between aggregates and fine powders is increased, making the two more closely combined, thereby improving the strength and thermal shock resistance of the castable. DETAILED DESCRIPTION
[0035] The following will be combined with the drawings in the embodiments of the present application to clearly and completely describe the technical solutions in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.
[0036] Pseudomonas stutzeri BBW831 is deposited in the China Center for Type Culture Collection; Pseudomonas denitrificans ATCC13867 is deposited in the Guangdong Provincial Center for Microbial Culture Collection.
[0037] In the following examples, if no specific conditions are specified, the experiments were carried out under conventional conditions or conditions recommended by the manufacturer. The reagents or instruments used were not specified by manufacturer and are all commercially available conventional products.
[0038] In the following examples, the specific raw material indicators are as follows:
[0039] Silica powder: SiO2 content ≥ 95wt%, particle size 1.0μm ~ 1.8μm; Al2O3 content in pure calcium aluminate cement ≥ 80wt%.
[0040] The particle size of expanded perlite is 0.5-2.8mm, the particle size of ceramsite is 0.5-6mm, the particle size of fly ash is 1.5-5μm, the particle size of the coke fine powder is 0.1-1mm, the particle size of calcium carbonate micropowder is 100-130 mesh, and the particle size of kyanite fine powder is 80-120 mesh.
[0041] The water reducer is a mixture of FDN high-efficiency water reducer, calcium lignin sulfonate and sodium tripolyphosphate, and the weight ratio of the FDN high-efficiency water reducer, calcium lignin sulfonate and sodium tripolyphosphate is (4.5-6):(1-1.5):(2-3).
[0042] The length of the short fiber flocs in the short-cut zirconium-containing refractory fibers is 5 to 10 mm; the heat-resistant stainless steel fibers are heat-resistant steel fibers containing nickel-chromium alloy elements; and the explosion-proof fibers are polypropylene fibers with a diameter of 1.5 to 3 μm and a length of 3 to 5 mm.
[0043] Example 1
[0044] A high-strength, lightweight, thermally insulating castable, characterized in that the castable comprises the following raw materials in parts by weight: 45 parts of modified expanded perlite, 30 parts of ceramsite, 6 parts of silica powder, 11 parts of pure calcium aluminate cement, 10 parts of fly ash, 8 parts of coke gemstone powder, 0.1 parts of water reducer, 0.12 parts of binder silica sol, 2 parts of short-cut zirconium-containing refractory fiber, 0.5 parts of heat-resistant stainless steel fiber, 0.8 parts of explosion-proof fiber, 5 parts of calcium carbonate powder, and 8 parts of kyanite powder. The mass ratio of modified expanded perlite to ceramsite is 1.5:1.
[0045] The preparation method of modified expanded perlite is as follows:
[0046] (1) inoculating a strain of nitrifying bacteria onto a tryptic protein culture medium, culturing the culture medium at a temperature of 25 to 35° C. for 18 to 24 hours, and then centrifuging the tryptic protein culture medium to obtain denitrifying bacteria, adding distilled water to the obtained denitrifying bacteria and mixing them evenly to obtain a bacterial solution of the denitrifying bacteria;
[0047] (2) soaking the expanded perlite in the bacterial solution of denitrifying bacteria obtained in step (1) for 18 hours, adding calcium ion nutrient solution to the bacterial solution, and continuing to soak for 8 hours, then taking out the expanded perlite, washing, drying, and setting aside;
[0048] (3) The expanded perlite washed and dried in step (2) is spread in a glass container of 30 cm in length×20 cm in width×9 cm in height, and then the surface of the expanded perlite is sprayed with a denitrifying bacteria solution and a calcium ion nutrient solution of the same concentration as in step (2) in sequence, once every 6 hours, and sprayed 4 times to obtain modified expanded perlite.
[0049] The concentration of denitrifying bacteria in the denitrifying bacteria solution is 2×10 8 ~4×10 8 cfu / mL; the denitrifying bacteria was Pseudomonas stutzeri BBW831.
[0050] The calcium ion nutrient solution is a mixture of 25-50 g / L calcium acetate, 15-25 g / L calcium nitrate and 1-12 g / L glucose, wherein the mass ratio of carbon and nitrogen in the calcium ion nutrient solution is (4-8):1, and the solvent of the calcium ion nutrient solution is distilled water; the mass ratio of the denitrifying bacteria liquid to the calcium ion nutrient solution is 1:(1-1.5).
[0051] A method for preparing a high-strength lightweight thermal insulation castable comprises the following steps:
[0052] Step S1, preparing materials according to the raw material components and weight proportions of high-strength lightweight thermal insulation castable;
[0053] Step S2, adding the modified expanded perlite, calcium carbonate powder, kyanite powder, part of the binder silica sol, and part of the pure calcium aluminate cement into a mixer according to the weight percentage prepared in step S1, stirring and mixing evenly to obtain a mixture, drying the mixture at 80° C. for 15 hours, cooling to room temperature after drying, and obtaining a pre-synthesized lightweight aggregate; wherein the part of the binder silica sol accounts for 1 / 3 of the total weight of the binder silica sol, and the part of the pure calcium aluminate cement accounts for 1 / 4 of the total weight of the pure calcium aluminate cement;
[0054] Step S3, mixing the remaining raw materials with the pre-synthesized lightweight aggregate obtained in step S2 in a corresponding proportion to obtain a high-strength lightweight thermal insulation castable.
[0055] Example 2
[0056] A high-strength, lightweight, thermally insulating castable, characterized in that the castable comprises the following raw materials in parts by weight: 40 parts of modified expanded perlite, 30 parts of ceramsite, 4 parts of silica powder, 8 parts of pure calcium aluminate cement, 13 parts of fly ash, 5 parts of coke gemstone powder, 0.12 parts of water reducer, 0.1 parts of binder silica sol, 3 parts of short-cut zirconium-containing refractory fiber, 0.7 parts of heat-resistant stainless steel fiber, 1 part of explosion-proof fiber, 4 parts of calcium carbonate powder, and 10 parts of kyanite powder. The mass ratio of modified expanded perlite to ceramsite is 1.14:1.
[0057] The preparation method of modified expanded perlite is as follows:
[0058] (1) inoculating a strain of nitrifying bacteria onto a tryptic protein culture medium, culturing the culture medium at a temperature of 25 to 35° C. for 18 to 24 hours, and then centrifuging the tryptic protein culture medium to obtain denitrifying bacteria, adding distilled water to the obtained denitrifying bacteria and mixing them evenly to obtain a bacterial solution of the denitrifying bacteria;
[0059] (2) soaking the expanded perlite in the bacterial solution of denitrifying bacteria obtained in step (1) for 20 hours, adding calcium ion nutrient solution to the bacterial solution, and continuing to soak for 9 hours, then taking out the expanded perlite, washing, drying, and setting aside;
[0060] (3) The expanded perlite washed and dried in step (2) is spread in a glass container of 30 cm in length×20 cm in width×9 cm in height, and then the surface of the expanded perlite is sprayed with a denitrifying bacteria solution and a calcium ion nutrient solution of the same concentration as in step (2) in sequence, once every 6.5 hours, and sprayed 5 times to obtain modified expanded perlite.
[0061] The concentration of denitrifying bacteria in the denitrifying bacteria solution is 2×10 8 ~4×10 8 cfu / mL; the denitrifying bacteria was Pseudomonas denitrificans ATCC13867.
[0062] The calcium ion nutrient solution is a mixture of 25-50 g / L calcium acetate, 15-25 g / L calcium nitrate and 1-12 g / L glucose, wherein the mass ratio of carbon and nitrogen in the calcium ion nutrient solution is (4-8):1, and the solvent of the calcium ion nutrient solution is distilled water; the mass ratio of the denitrifying bacteria liquid to the calcium ion nutrient solution is 1:(1-1.5).
[0063] A method for preparing a high-strength lightweight thermal insulation castable comprises the following steps:
[0064] Step S1, preparing materials according to the raw material components and weight proportions of high-strength lightweight thermal insulation castable;
[0065] Step S2, adding the modified expanded perlite, calcium carbonate powder, kyanite powder, part of the binder silica sol, and part of the pure calcium aluminate cement into a mixer according to the weight percentage prepared in step S1, stirring and mixing evenly to obtain a mixture, drying the mixture at 100° C. for 13 hours, cooling to room temperature after drying, and obtaining a pre-synthesized lightweight aggregate; wherein the part of the binder silica sol accounts for 1 / 3 of the total weight of the binder silica sol, and the part of the pure calcium aluminate cement accounts for 1 / 4 of the total weight of the pure calcium aluminate cement;
[0066] Step S3, mixing the remaining raw materials with the pre-synthesized lightweight aggregate obtained in step S2 in a corresponding proportion to obtain a high-strength lightweight thermal insulation castable.
[0067] Example 3
[0068] A high-strength, lightweight, thermally insulating castable, characterized in that the castable comprises the following raw materials in parts by weight: 35 parts of modified expanded perlite, 25 parts of ceramsite, 5 parts of silica powder, 10 parts of pure calcium aluminate cement, 15 parts of fly ash, 11 parts of coke gemstone powder, 0.15 parts of water reducer, 0.13 parts of binder silica sol, 3 parts of short-cut zirconium-containing refractory fiber, 0.9 parts of heat-resistant stainless steel fiber, 1.2 parts of explosion-proof fiber, 6 parts of calcium carbonate powder, and 12 parts of kyanite powder. The mass ratio of modified expanded perlite to ceramsite is 1.4:1.
[0069] The preparation method of modified expanded perlite is as follows:
[0070] (1) inoculating a strain of nitrifying bacteria onto a tryptic protein culture medium, culturing the culture medium at a temperature of 25 to 35° C. for 18 to 24 hours, and then centrifuging the tryptic protein culture medium to obtain denitrifying bacteria, adding distilled water to the obtained denitrifying bacteria and mixing them evenly to obtain a bacterial solution of the denitrifying bacteria;
[0071] (2) soaking the expanded perlite in the bacterial solution of denitrifying bacteria obtained in step (1) for 22 hours, adding calcium ion nutrient solution to the bacterial solution, and continuing to soak for 10 hours, then taking out the expanded perlite, washing, drying, and setting aside;
[0072] (3) The expanded perlite washed and dried in step (2) is spread in a glass container of 30 cm in length×20 cm in width×9 cm in height, and then the surface of the expanded perlite is sprayed with a denitrifying bacteria solution and a calcium ion nutrient solution of the same concentration as in step (2) in sequence, once every 7 hours, and sprayed 6 times to obtain modified expanded perlite.
[0073] The concentration of denitrifying bacteria in the denitrifying bacteria solution is 2×10 8 ~4×10 8 cfu / mL; the denitrifying bacteria was Pseudomonas denitrificans ATCC13867.
[0074] The calcium ion nutrient solution is a mixture of 25-50 g / L calcium acetate, 15-25 g / L calcium nitrate and 1-12 g / L glucose, wherein the mass ratio of carbon and nitrogen in the calcium ion nutrient solution is (4-8):1, and the solvent of the calcium ion nutrient solution is distilled water; the mass ratio of the denitrifying bacteria liquid to the calcium ion nutrient solution is 1:(1-1.5).
[0075] A method for preparing a high-strength lightweight thermal insulation castable comprises the following steps:
[0076] Step S1, preparing materials according to the raw material components and weight proportions of high-strength lightweight thermal insulation castable;
[0077] Step S2, adding the modified expanded perlite, calcium carbonate powder, kyanite powder, part of the binder silica sol, and part of the pure calcium aluminate cement into a mixer according to the weight percentage prepared in step S1, stirring and mixing evenly to obtain a mixture, drying the mixture at 180° C. for 10 hours, cooling to room temperature after drying, and obtaining a pre-synthesized lightweight aggregate; wherein the part of the binder silica sol accounts for 1 / 3 of the total weight of the binder silica sol, and the part of the pure calcium aluminate cement accounts for 1 / 4 of the total weight of the pure calcium aluminate cement;
[0078] Step S3, mixing the remaining raw materials with the pre-synthesized lightweight aggregate obtained in step S2 in a corresponding proportion to obtain a high-strength lightweight thermal insulation castable.
[0079] Example 4
[0080] A high-strength, lightweight, thermally insulating castable, characterized in that the castable comprises the following raw materials in parts by weight: 25 parts of modified expanded perlite, 20 parts of ceramsite, 8 parts of silica powder, 15 parts of pure calcium aluminate cement, 180 parts of fly ash, 15 parts of coke gemstone powder, 0.2 parts of water reducer, 0.14 parts of binder silica sol, 4 parts of short-cut zirconium-containing refractory fiber, 0.8 parts of heat-resistant stainless steel fiber, 1.5 parts of explosion-proof fiber, 8 parts of calcium carbonate powder, and 9 parts of kyanite powder. The mass ratio of modified expanded perlite to ceramsite is 1.25:1.
[0081] The preparation method of modified expanded perlite is as follows:
[0082] (1) inoculating a strain of nitrifying bacteria onto a tryptic protein culture medium, culturing the culture medium at a temperature of 25 to 35° C. for 18 to 24 hours, and then centrifuging the tryptic protein culture medium to obtain denitrifying bacteria, adding distilled water to the obtained denitrifying bacteria and mixing them evenly to obtain a bacterial solution of the denitrifying bacteria;
[0083] (2) soaking the expanded perlite in the bacterial solution of denitrifying bacteria obtained in step (1) for 23 hours, adding calcium ion nutrient solution to the bacterial solution, and continuing to soak for 11 hours, then taking out the expanded perlite, washing, drying, and setting aside;
[0084] (3) The expanded perlite washed and dried in step (2) is spread in a glass container of 30 cm in length×20 cm in width×9 cm in height, and then the surface of the expanded perlite is sprayed with a denitrifying bacteria solution and a calcium ion nutrient solution of the same concentration as in step (2) in sequence, once every 7.5 hours, and sprayed 5 times to obtain modified expanded perlite.
[0085] The concentration of denitrifying bacteria in the denitrifying bacteria solution is 2×10 8 ~4×10 8 cfu / mL; the denitrifying bacteria was Pseudomonas stutzeri BBW831.
[0086] The calcium ion nutrient solution is a mixture of 25-50 g / L calcium acetate, 15-25 g / L calcium nitrate and 1-12 g / L glucose, wherein the mass ratio of carbon and nitrogen in the calcium ion nutrient solution is (4-8):1, and the solvent of the calcium ion nutrient solution is distilled water; the mass ratio of the denitrifying bacteria liquid to the calcium ion nutrient solution is 1:(1-1.5).
[0087] A method for preparing a high-strength lightweight thermal insulation castable comprises the following steps:
[0088] Step S1, preparing materials according to the raw material components and weight proportions of high-strength lightweight thermal insulation castable;
[0089] Step S2, adding the modified expanded perlite, calcium carbonate powder, kyanite powder, part of the binder silica sol, and part of the pure calcium aluminate cement into a mixer according to the weight percentage prepared in step S1, stirring and mixing evenly to obtain a mixture, drying the mixture at 150° C. for 12 hours, cooling to room temperature after drying, and obtaining a pre-synthesized lightweight aggregate; wherein the part of the binder silica sol accounts for 1 / 3 of the total weight of the binder silica sol, and the part of the pure calcium aluminate cement accounts for 1 / 4 of the total weight of the pure calcium aluminate cement;
[0090] Step S3, mixing the remaining raw materials with the pre-synthesized lightweight aggregate obtained in step S2 in a corresponding proportion to obtain a high-strength lightweight thermal insulation castable.
[0091] Example 5
[0092] A high-strength, lightweight, thermally insulating castable, characterized in that the castable comprises the following raw materials in parts by weight: 30 parts of modified expanded perlite, 10 parts of ceramsite, 3 parts of silica powder, 12 parts of pure calcium aluminate cement, 20 parts of fly ash, 13 parts of coke gemstone powder, 0.17 parts of water reducer, 0.15 parts of binder silica sol, 2 parts of short-cut zirconium-containing refractory fiber, 1 part of heat-resistant stainless steel fiber, 1.3 parts of explosion-proof fiber, 7 parts of calcium carbonate powder, and 11 parts of kyanite powder. The mass ratio of modified expanded perlite to ceramsite is 3:1.
[0093] The preparation method of modified expanded perlite is as follows:
[0094] (1) inoculating a strain of nitrifying bacteria onto a tryptic protein culture medium, culturing the culture medium at a temperature of 25 to 35° C. for 18 to 24 hours, and then centrifuging the tryptic protein culture medium to obtain denitrifying bacteria, adding distilled water to the obtained denitrifying bacteria and mixing them evenly to obtain a bacterial solution of the denitrifying bacteria;
[0095] (2) soaking the expanded perlite in the bacterial solution of denitrifying bacteria obtained in step (1) for 24 hours, adding calcium ion nutrient solution to the bacterial solution, and continuing to soak for 12 hours, then taking out the expanded perlite, washing, drying, and setting aside;
[0096] (3) The expanded perlite washed and dried in step (2) is spread in a glass container of 30 cm in length×20 cm in width×9 cm in height, and then the surface of the expanded perlite is sprayed with a denitrifying bacteria solution and a calcium ion nutrient solution of the same concentration as in step (2) in sequence, once every 8 hours, and sprayed 6 times to obtain modified expanded perlite.
[0097] The concentration of denitrifying bacteria in the denitrifying bacteria solution is 2×10 8 ~4×10 8 cfu / mL; the denitrifying bacteria was Pseudomonas denitrificans ATCC13867.
[0098] The calcium ion nutrient solution is a mixture of 25-50 g / L calcium acetate, 15-25 g / L calcium nitrate and 1-12 g / L glucose, wherein the mass ratio of carbon and nitrogen in the calcium ion nutrient solution is (4-8):1, and the solvent of the calcium ion nutrient solution is distilled water; the mass ratio of the denitrifying bacteria liquid to the calcium ion nutrient solution is 1:(1-1.5).
[0099] A method for preparing a high-strength lightweight thermal insulation castable comprises the following steps:
[0100] Step S1, preparing materials according to the raw material components and weight proportions of high-strength lightweight thermal insulation castable;
[0101] Step S2, adding the modified expanded perlite, calcium carbonate powder, kyanite powder, part of the binder silica sol, and part of the pure calcium aluminate cement into a mixer according to the weight percentage prepared in step S1, stirring and mixing evenly to obtain a mixture, drying the mixture at 200° C. for 8 hours, cooling to room temperature after drying, and obtaining a pre-synthesized lightweight aggregate; wherein the part of the binder silica sol accounts for 1 / 3 of the total weight of the binder silica sol, and the part of the pure calcium aluminate cement accounts for 1 / 4 of the total weight of the pure calcium aluminate cement;
[0102] Step S3, mixing the remaining raw materials with the pre-synthesized lightweight aggregate obtained in step S2 in a corresponding proportion to obtain a high-strength lightweight thermal insulation castable.
[0103] Comparative Example 1
[0104] In this comparative example, the modified expanded perlite is replaced by an equal mass of ordinary unmodified expanded perlite; the other raw material components of the castable and the corresponding weight proportions, as well as the castable preparation method are the same as those in Example 3.
[0105] Comparative Example 2
[0106] In this comparative example, when preparing the modified expanded perlite, the time for soaking the expanded perlite in the denitrifying bacteria solution and the denitrifying bacteria solution with added calcium ion nutrient solution in step (2) is 16 hours and 6 hours respectively; or the time for soaking the expanded perlite in the denitrifying bacteria solution and the denitrifying bacteria solution with added calcium ion nutrient solution in step (2) is 26 hours and 14 hours respectively; the raw material components of the castable and the corresponding weight parts, as well as the preparation method of the denitrifying bacteria and the castable preparation method are the same as those in Example 3.
[0107] Comparative Example 3
[0108] In the present comparative example, when preparing the modified expanded perlite, in step (3), the surface of the expanded perlite that has been washed and dried in step (2) is directly sprayed with a denitrifying bacteria solution and a calcium ion nutrient solution of the same concentration as in step (2) in sequence; the raw material components of the castable and the corresponding weight proportions, as well as the preparation method of the denitrifying bacteria and the preparation method of the castable are the same as those in Example 3.
[0109] Comparative Example 4
[0110] In this comparative example, when preparing the modified expanded perlite, step (3) is directly omitted, and the raw material components of the castable and the corresponding weight proportions, as well as the preparation method of the denitrifying bacteria and the castable preparation method are the same as those in Example 3.
[0111] Comparative Example 5
[0112] In this comparative example, a modified expanded perlite is obtained by coating a layer of polystyrene pre-coating on the surface of the expanded perlite; the raw material components and corresponding weight portions of the castable, as well as the castable preparation method are the same as those in Example 3.
[0113] Comparative Example 6
[0114] In this comparative example, the weight proportion of the modified expanded perlite is 25 parts, the weight proportion of the expanded ceramsite is 35 parts, and the mass ratio of the modified expanded perlite to the expanded ceramsite is 0.71:1; the other raw material components of the castable and the corresponding weight proportions, as well as the preparation method of the denitrifying bacteria, the preparation method of the modified perlite and the preparation method of the castable are the same as those in Example 3.
[0115] The castables obtained in Examples 1 to 5 and Comparative Examples 1 to 6 were added with 5% water of the total mass of the castables, stirred evenly, and heat treated at 1450°C × 3h. The bulk density was tested by the liquid static weighing method according to YB / T 5200-93 "Test method for apparent porosity and bulk density of dense refractory castables"; the volume water absorption was tested by referring to the method of GB / T 2997-1983 "Determination method for water absorption of dense shaped refractory products"; the flexural strength was tested by referring to the method of GB / T 3001-2017 "Test method for flexural strength of refractory materials at room temperature"; the compressive strength was tested by referring to the method of GB / T 5072-2008 "Test method for compressive strength of refractory materials at room temperature"; the thermal conductivity was tested by referring to the method of GB / T5990-2006 "Test method for thermal conductivity of refractory materials"; the specific test results are shown in Table 1.
[0116] Table 1 Performance parameters of the castables obtained in Examples 1 to 5 and Comparative Examples 1 to 6
[0117]
[0118] From the comparison of the performance data of Comparative Example 1 and Example 3 in Table 1, it can be found that by using the modified expanded perlite as the main aggregate of the castable, although the bulk density of the castable is slightly increased, the water absorption and thermal conductivity of the castable are significantly reduced, and the flexural strength and compressive strength of the castable are significantly improved. This is mainly because the calcium ions in the denitrifying bacteria solution and the calcium ion nutrient solution are mineralized and deposited in the pores inside or on the surface of the expanded perlite to produce calcium carbonate. The calcium carbonate fills part of the pores inside the expanded perlite, significantly improves the strength of the aggregate, and reduces the water absorption of the aggregate. By comparing the performance data of Comparative Example 2 with that of Example 3, it can be found that when the expanded perlite is immersed in the denitrifying bacterial solution for a short time, the amount of adsorption of the bacterial solution in the perlite pores is small, resulting in a small amount of calcium carbonate generated, and the pores of the perlite cannot be filled well; when the immersion time is too long, the bacterial solution may lose its activity and lose the ability to mineralize and deposit calcium carbonate, resulting in the inability to fill the pores of the expanded perlite. If the immersion time of the expanded perlite is too short or too long, the calcium ion nutrient solution or the denitrifying bacterial solution may be adsorbed on the expanded perlite, and the pores of the expanded perlite are not filled. Instead, the bulk density of the expanded perlite is increased, thereby reducing the mechanical properties and thermal insulation properties of the castable. Comparison of the performance data of Comparative Example 3 with that of Example 3 shows that, in the step (3) of modifying the expanded perlite, the perlite must first be laid flat in a glass container, and then the denitrifying bacteria solution and the calcium ion nutrient solution are sequentially sprayed onto the surface of the perlite. This makes up for the defect that some expanded perlite in step (2) floats on the surface of the bacteria solution or is squeezed together, resulting in the internal and surface pores of the expanded perlite not being filled. On the other hand, the number and frequency of spraying can be controlled to ensure that the amount of calcium carbonate generated is not excessive, which leads to an increase in the bulk density of the expanded perlite, thereby improving the flexural strength, compressive strength and thermal insulation performance of the castable. 3. By comparing the performance data of the invention, it can be found that the present invention adopts the method of first soaking and then spraying the bacterial solution to modify the perlite so that the bacterial solution is adsorbed in the internal or surface pores of the perlite, which to a certain extent avoids the instantaneous contact charge mutual repulsion and the inability to attach caused by the negative charge on the surface of the expanded perlite and the negative charge on the denitrifying bacteria themselves, and can ensure that the denitrifying bacteria provide more nucleation sites, so that more calcium carbonate is precipitated on the surface and internal pores of the expanded perlite, filling the pores of the expanded perlite, thereby reducing the water absorption rate of the expanded perlite and improving its mechanical properties. When the modified expanded perlite is used as the main aggregate of the castable, the mechanical properties of the castable are improved.By comparing the performance data of Comparative Example 6 with that of Example 3, it can be found that although the use of organic polymer to coat the expanded perlite has obvious improvements in the strength and water absorption of the expanded perlite, this modification treatment increases the bulk density of the expanded perlite to a certain extent, thereby increasing the volume density of the castable as an aggregate, thereby causing the thermal conductivity of the castable to increase and the thermal insulation performance to decrease. By comparing the performance data of Comparative Example 6 with that of Example 3, it can be found that the modified expanded perlite is combined with ceramsite to obtain a composite aggregate. By optimizing the addition ratio of the two lightweight aggregates and their coupled synergistic effect, stable support of the aggregate in the castable is achieved, and the strength, thermal shock stability and thermal insulation performance of the castable are improved. Moreover, CaO, MgO and Na2O in the ceramsite can act as sintering aids, which is beneficial to the sintering densification of the castable. The addition of an appropriate amount of ceramsite can react with the modified perlite to generate CaSiO3, which has high strength and durability, and can improve the compressive strength and thermal shock resistance of the castable. However, the addition of excessive ceramsite will deteriorate the hydration effect of pure calcium aluminate cement, reduce the binding phase between aggregates, and cause the compressive strength of the castable to decrease.
[0119] In summary, the present application utilizes microbial mineralization to modify expanded perlite, and the modified expanded perlite is mixed with calcium carbonate powder, kyanite powder, silica sol, and pure calcium aluminate cement to prepare a pre-synthesized lightweight aggregate, which significantly improves the strength of the aggregate and reduces the water absorption of the aggregate, thereby also improving the mechanical properties and refractory thermal insulation properties of the castable to a certain extent. In particular, when the castable is used at high temperature (above 900°C), the calcium carbonate powder added in the present application is decomposed at high temperature to obtain CaO, which reacts with alumina in pure calcium aluminate cement in situ to generate calcium hexaaluminate after high-temperature calcination, and the particle size of calcium hexaaluminate is much finer. , and the dispersibility of the generated flaky calcium hexaaluminate is greatly improved, so that a large number of evenly distributed tiny voids and cracks are formed in the castable matrix; at the same time, in the process of calcium carbonate powder decomposing to generate CaO and CO2 at high temperature, the escape of CO2 leads to the formation of a large number of evenly distributed micropores in the castable system, thereby significantly improving the thermal shock stability of the castable; at the same time, the pre-synthesized lightweight aggregate and an appropriate amount of ceramsite are composited as the main lightweight aggregate of the castable. By optimizing the addition ratio of the two lightweight aggregates and their coupling synergistic effect, the stable support of the aggregate in the castable is achieved, and the strength, thermal shock stability and thermal insulation performance of the castable are improved. By adding pure calcium aluminate cement, silica sol and silica powder as binders, the mechanical properties of aggregates are improved; pure calcium aluminate cement, silica sol and silica powder are used as composite binders to improve the bonding performance between aggregates, and at the same time, the high-temperature strength and thermal shock resistance of the castable can be improved; and coke powder and fly ash powder with high hardness and high refractoriness are used as fine powders to fill the gaps between aggregates. Due to the uneven surface of the aggregate, the contact specific surface area between the aggregate and the fine powder is increased, making the two more closely bonded, thereby improving the strength and thermal shock resistance of the castable.
[0120] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.
[0121] Although the embodiments of the present application have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present application, and that the scope of the present application is defined by the appended claims and their equivalents.
Claims
1. A high-strength, lightweight, thermally insulating castable, characterized in that: The castable comprises the following raw materials in weight percentage: 20-45 parts of modified expanded perlite, 10-35 parts of ceramsite, 3-8 parts of silica powder, 8-15 parts of pure calcium aluminate cement, 10-20 parts of fly ash, 5-15 parts of coke gemstone powder, 0.1-0.2 parts of water reducer, 0.1-0.15 parts of silica sol as binder, 2-4 parts of short-cut zirconium-containing refractory fiber, 0.5-1 parts of heat-resistant stainless steel fiber, 0.8-1.5 parts of explosion-proof fiber, 4-8 parts of calcium carbonate powder, and 8-12 parts of kyanite powder; the mass ratio of the modified expanded perlite to the ceramsite is (1.1-3):1; The preparation method of the modified expanded perlite is specifically as follows: (1) Soaking the expanded perlite in a bacterial solution of denitrifying bacteria for 18 to 24 hours, adding a calcium ion nutrient solution to the bacterial solution, and continuing to soak for 8 to 12 hours, then taking out the expanded perlite, washing it, drying it, and setting it aside; (2) The expanded perlite washed and dried in step (1) is spread flat in a glass container of 30 cm in length × 20 cm in width × 9 cm in height, and then the surface of the expanded perlite is sprayed with a denitrifying bacteria solution and a calcium ion nutrient solution of the same concentration as in step (1) in sequence, once every 6 to 8 hours, and sprayed 4 to 6 times to obtain modified expanded perlite.
2. A high-strength lightweight thermal insulation castable according to claim 1, characterized in that: The denitrifying bacteria liquid is prepared by the following method: inoculating the denitrifying bacteria strains onto a trypsin culture medium, culturing at a temperature of 25 to 35° C. for 18 to 24 hours, then centrifuging the culture medium to obtain denitrifying bacteria, adding distilled water to the obtained denitrifying bacteria and mixing them evenly to obtain the denitrifying bacteria liquid.
3. A high-strength, lightweight, thermally insulating castable according to claim 1, characterized in that: The concentration of denitrifying bacteria in the denitrifying bacteria solution is 2×10 8 ~4×10 8 cfu / mL; the denitrifying bacteria are Pseudomonas stutzeri BBW831 or Take off Pseudomonas aeruginosa ATCC13867.
4. A high-strength, lightweight, thermally insulating castable according to claim 1, characterized in that: The calcium ion nutrient solution is a mixture of 25-50 g / L calcium acetate, 15-25 g / L calcium nitrate and 1-12 g / L glucose, wherein the mass ratio of carbon to nitrogen in the calcium ion nutrient solution is (4-8):1, and the solvent of the calcium ion nutrient solution is distilled water; the mass ratio of the denitrifying bacteria liquid to the calcium ion nutrient solution is 1:(1-1.5).
5. The high-strength lightweight thermal insulation castable according to claim 1, characterized in that: The silicon micropowder: SiO2 content ≥95wt%, particle size 1.0μm~1.8μm; the Al2O3 content in the pure calcium aluminate cement ≥80wt%; the particle size of the expanded perlite is 0.5~2.8mm; the particle size of the ceramsite is 0.5~6mm; the particle size of the fly ash is 1.5~5μm; the particle size of the pyrope fine powder is 0.1~1mm; the particle size of the calcium carbonate micropowder is 100~130 mesh; the particle size of the kyanite fine powder is 80~120 mesh.
6. The high-strength lightweight thermal insulation castable according to claim 1, characterized in that: The length of the short fiber flocs in the short-cut zirconium-containing refractory fibers is 5 to 10 mm; the heat-resistant stainless steel fibers are heat-resistant steel fibers containing nickel-chromium alloy elements; and the explosion-proof fibers are polypropylene fibers with a diameter of 1.5 to 3 μm and a length of 3 to 5 mm.
7. The high-strength lightweight thermal insulation castable according to claim 1, characterized in that: The water reducer is a composite water reducer, which is a mixture of FDN high-efficiency water reducer, calcium lignin sulfonate and sodium tripolyphosphate, and the mass ratio of the FDN high-efficiency water reducer, calcium lignin sulfonate and sodium tripolyphosphate is (4.5-6):(1-1.5):(2-3).
8. A method for preparing a high-strength lightweight thermal insulation castable according to any one of claims 1 to 7, characterized in that: The following steps are involved: Step S1, preparing materials according to the raw material components and weight percentages of high-strength lightweight thermal insulation castable; Step S2, adding the modified expanded perlite, calcium carbonate powder, kyanite powder, part of the binder silica sol, and part of the pure calcium aluminate cement into a mixer according to the weight percentage prepared in step S1, stirring and mixing evenly to obtain a mixture, drying the mixture at 80-200° C. for 8-15 hours, cooling to room temperature after drying, and obtaining a pre-synthesized lightweight aggregate; wherein the part of the binder silica sol accounts for 1 / 3 of the total weight of the binder silica sol, and the part of the pure calcium aluminate cement accounts for 1 / 4 of the total weight of the pure calcium aluminate cement; Step S3, mixing the remaining raw materials with the pre-synthesized lightweight aggregate obtained in step S2 in a corresponding proportion to obtain a high-strength lightweight thermal insulation castable.
